Plasma cell granuloma of gingiva - Balaji Manohar; S Bhuvaneshwari (Wolters Kluwer Medknow Publications, 2011)
Plasma cell granuloma is a rare benign lesion characterized by the infiltration of plasma cells; primarily occurring in the lungs. It is also seen to occur in the brain, kidney stomach, heart, and so on. In the intraoral region it is seen to involve the tongue, oral mucosa, and gingiva. This case presents a 42-year-old female, with an enlargement in the maxillary anterior region, treated by excisional biopsy. Histological evaluation revealed plasma cell infiltrates in the connective tissue. The immunohistochemistry revealed kappa and lambda light chains with a polyclonal staining pattern, which confirmed the diagnosis of plasma cell granuloma.